ELT Solutions: Marketing Strategies for Effective Language Teaching and Education Management - Mirsa Umiyati; Morteza Azarpira; Epos Sister Selan Krismon Dakhi (Warmadewa Press, 2024)
Community service research in English Language Teaching (ELT) is instrumental in evolving language education and refining management strategies. This research aims 1) to conduct a comprehensive assessment of the current landscape of language education, 2) to identify the diverse needs and preferences of language learners across various demographics, and 3) to develop marketing approaches that foster inclusivity in language education. The research methodology leverages the Zoom platform, offering a versatile virtual environment for stakeholder consultations, remote workshops, training sessions, and community engagement. The integration of Zoom proves effective in maintaining consistent communication, monitoring progress, and gathering real-time insights from diverse perspectives. The results of the community service activities are impactful, achieving a comprehensive assessment of the current language education landscape, identification of diverse learner needs, and the development of inclusive marketing approaches. The virtual nature of Zoom workshops facilitates the dissemination of inclusive strategies, contributing to a collaborative and supportive community within language education. In conclusion, ELT Solutions’ community service research, guided by innovative marketing strategies and facilitated by Zoom, significantly contributes to the improvement of language instruction, identification of diverse learner needs, and the development of inclusive practices. As a beacon for ongoing evolution in language education, this research positively impacts global language proficiency and intercultural communication skills, emphasizing the importance of adaptability in effective language teaching and education management.